2014
DOI: 10.1007/s00192-014-2496-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myogenic stem cells on the integrity and histomorphology of repaired transected external anal sphincter

Abstract: In this animal model, administration of myogenic stem cells to transected/repaired anal sphincters did not alter the amount of inflammation nor the volume of striated muscle, suggesting that stem cells might improve contractile function through other cellular processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 10 publications
0
36
0
1
Order By: Relevance
“…13 at the time of acute injury, the tissues attract growth factors and exhibit subsequent inflammation and fibrosis. 26 however, symptoms often occur much later after anal sphincter trauma. the site of injury, at a time remote from acute trauma, does not demonstrate the environment that occurs at the time of injury.…”
Section: Discussionmentioning
confidence: 98%
“…13 at the time of acute injury, the tissues attract growth factors and exhibit subsequent inflammation and fibrosis. 26 however, symptoms often occur much later after anal sphincter trauma. the site of injury, at a time remote from acute trauma, does not demonstrate the environment that occurs at the time of injury.…”
Section: Discussionmentioning
confidence: 98%
“…Fitzwater et al . proposed that administration of myogenic stem cells improves the contractile function of the EAS through cellular mechanisms other than muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…White and coworkers [10] found that injection of myogenic stem cells with EAS repair resulted in enhanced contractile function at 3 months compared with repair alone. Fitzwater et al [11] proposed that administration of myogenic stem cells improves the contractile function of the EAS through cellular mechanisms other than muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Pathi et al, on the other hand, did not find significant advantage in the iv-administration of rat bonemarrow derived MSCs compared with the PBS controls, but the local injections of MSCs were effective according to in vitro assessment [17]. Recently Fitzwater et al noticed that the administration of rat myogenic stem cells enhanced the contractile function of the sphincter without significant changes in histologic morphology, which addresses the paracrine processes in stem cell therapy [14]. To simplify the cell isolation and proliferation process, Mazzanti et al used freshly isolated minimally manipulated bonemarrow derived mononuclear cells without expansion and found them to be as effective as in vitro expanded BM-MSCs in the recovery of iatrogenic anal sphincter rupture [38].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies concerning stem cells in the treatment of anal sphincter defects. Rat models with muscle-derived stem cells or myoblasts as the stem cell origin are the most common study designs [10][11][12][13][14], although bigger animals (rabbits, dogs) have been used as well [15,16]. Mesenchymal stem cells (MSC) derived from bone marrow have been used in a few studies and the results are promising [17][18][19].…”
Section: Introductionmentioning
confidence: 99%